La política asistencial bajo el modelo social de la discapacidad en Michoacán, 2012-2018 - Guzmán Pimentel, Elizabeth (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
The general objective of this study is to determine how inclusion, social integration and welfare policy affect the social welfare of people with disabilities (PWD) in Michoacán. Therefore, a questionnaire with a Likert-type scale was constructed. The data was analyzed with the Statistical Package for the Social Sciences (SPSS), secondary data, life histories, interviews, participant observation and evaluation of the public policy design for attention to PWD also studied. The result of the methodology shows positive outcomes of the three variables for social well-being, although if they are studied excluding some indicators such as subjective well-being, the indices reflect that effectively the care policy does not have a positive correlation, not so for the cases of inclusion variables and social integration. This means that the greater the inclusion and social integration, the greater the social welfare, but it does not have the same result for the welfare policy in Michoacán. Finally, and with the results of the methodology, a public policy proposal with a social approach to disability is presented based on the evidence obtained in this investigation.

La presente investigación tiene como objetivo general, determinar cómo es que incidieron la inclusión, integración social y política asistencial en el bienestar social de las personas con alguna discapacidad en Michoacán. Por lo anterior, se construyó un cuestionario con Escala tipo Likert. Los datos se analizaron con el Paquete Estadístico para las Ciencias Sociales (SPSS), también se estudiaron datos secundarios, historias de vida, entrevistas, observación participante y evaluación al diseño de PP para atención a PCD. El resultado de la metodología muestra correlación positiva de las tres variables para el bienestar social, aunque si se estudian excluyendo algunos indicadores como el bienestar subjetivo, los índices reflejan que efectivamente la política asistencial no tiene una correlación positiva, no así para los casos de variables inclusión e integración social. Lo que significa que a mayor inclusión e integración social mayor bienestar social, pero no tiene el mismo resultado para la política asistencial en Michoacán. Por último, y atendiendo los resultados de la metodología, se presenta una propuesta de política pública con enfoque social para la discapacidad a partir de la evidencia aquí obtenida.
Instituto de Investigaciones Económicas y Empresariales. Doctorado en Políticas Públicas
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4004; info:eu-repo/classification/cti/5; ININEE-D-2021-0696; Asistencia social; Integración social; Bienestar social